INSERTION OF DISSOLVED ORGANIC MATTER BASED OF PROBIOTICS WITH DIFFERENT DOSAGES IN AQUACULTURE MEDIA TO KELABAU FISH (Osteochillus melanopleura) LARVAE SURVIVAL - Rini Marlida; Rina Iskandar; Ika Purnama Sari (Universitas Mataram, 2025)
Kelabau fish (Osteochilus melanopleura) is an economically important fish in South Kalimantan. The obstacle that is still often encountered in its cultivation is the low survival of the larvae produced. The aim of this study was to determine the best probiotic dose for survival of kelabau fish (O. melanopleura) larvae. This research was conducted for 3 (three) months. The place of research is the Freshwater Aquaculture Fishery Center (BPBAT) Mandiangin, Karang Intan District, South Kalimantan Province. This study used an experimental method using a complete randomized design (CRD) with three treatments and three replications. Treatment A was given dissolved organic matter in the form of probiotics 0 ml/L (as a control), treatment B was given 0.5 ml/L, treatment C was given 1 ml/L. The water used in the research containers was filled with 3 liters of water each with a water level of 15.9 cm and a stocking density of 45 larvae in each treatment. The results of the research showed that the survival rate of kelabau fish larvae in treatment A was 95.24%, treatment B was 96.03%, treatment C was 96.83%. The survival Anova test results obtained that administration of probiotic-based dissolved organic matter has no effect on survival of larvae. The results of water quality measurements for temperature and pH parameters can be said to be good for the maintenance and survival of kelabau fish larvae during observation.